Religiosity and crime: evidence from a city-wide shock - Lee, Wang-Sheng (Discussion paper series, 2024)
This paper estimates the impacts of religiosity on criminal activity using a city-wide shock to religious sentiment from a 2015 Papal visit. Using daily data on all reported offences between 2010 and 2015 in Philadelphia at the census tract level and a difference-in-differences approach, we demonstrate significant reductions in less serious crimes in the week of the visit and for several weeks following. Reductions are particularly pronounced for drug offences and in historically Christian areas. Notably, similar crime effects are not found for President Obama's 2015 visit, suggesting changes in police deployment do not drive results.